Kelayakan Finansial Budidaya Tanaman Rimpang di Masa Pandemi Covid 19 - Gandhi, Prima (Fakultas Pertanian, Universitas Timor, 2024)
The agricultural sector is one of the supporting sectors of the Indonesian economy during the Covid-19 pandemic. Horticulture is one of the agricultural sub-sectors that contributes significantly to the national economy. Biopharmaceutical plants are part of the horticulture sub-sector and are used as raw materials for health products. Ginger, turmeric, galangal, kencur, and temulawak are five biopharmaceutical plants of the rhizome group that can be used as herbal medicines to anticipate some symptoms of Covid-19. One of the cultivators of these five biopharmaceutical plants is Taman Sringganis. The problem faced is that the cultivation of medicinal plants in the rhizome group is not optimal due to the many types of medicinal plants being cultivated. The financial feasibility of cultivation must be known To optimize the cultivation of rhizome plants. This research was conducted to determine the feasibility of cultivating medicinal plants in the rhizome group. As a result, during the Covid-19 pandemic, the cultivation of Taman Sringganis rhizomes was still feasible. Based on the calculation results of the four investment feasibility criteria, it is known that the Net Present Value (NPV) is positive or more than equal to zero, namely Rp. 258,213,256, the Net Benefit Cost Ratio (Net B/C Ratio) is more than one, namely 1.79, the Internal Rate of Return (IRR) is more than the predetermined social interest rate (10.1%), namely 36% and Payback Period (PP) is faster than the business age (5 years) which is 3 years 4 months. Rhizome, medicinal plant cultivation, supports the 8th SDGs.